2015
DOI: 10.1111/apa.13094
|View full text |Cite
|
Sign up to set email alerts
|

Reading deficits in very low birthweight children are associated with vocabulary and attention issues at the age of seven

Abstract: AimThis Swedish study compared reading skills between seven‐year‐old children with a very low birthweight (VLBW) and controls with a normal birthweight, exploring associations between reading variables and cognition, parent‐rated behaviour, perinatal factors and family factors.MethodsWe studied 51 VLBW children, with no major neurodevelopmental impairments and attending their first year at a regular school, and compared them with the 51 sex‐ and age‐matched controls. The test battery, carried out at 7.8 ± 0.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 27 publications
(27 reference statements)
3
19
2
Order By: Relevance
“…Most studies on reading abilities in preterm children (PT) were carried out with very preterm (VPT) or extremely preterm (EPT) children (gestational age < 32 weeks), and the results indicate that school-aged PT children obtain significantly lower results than full-term children (FT) in decoding abilities (Anderson et al, 2003;Johnson et al, 2012Johnson et al, , 2016Taylor et al, 2016;Alanko et al, 2017;Guarini et al, 2019), reading comprehension (Lee et al, 2011) or in both decoding abilities and reading comprehension (Pritchard et al, 2009(Pritchard et al, , 2014Johnson et al, 2011;Leijon et al, 2016Leijon et al, , 2018. Similar results were found in two metaanalyses (Aarnoudse-Moens et al, 2009;Kovachy et al, 2015).…”
Section: Reading and Associated Abilities In Preterm Childrenmentioning
confidence: 63%
“…Most studies on reading abilities in preterm children (PT) were carried out with very preterm (VPT) or extremely preterm (EPT) children (gestational age < 32 weeks), and the results indicate that school-aged PT children obtain significantly lower results than full-term children (FT) in decoding abilities (Anderson et al, 2003;Johnson et al, 2012Johnson et al, , 2016Taylor et al, 2016;Alanko et al, 2017;Guarini et al, 2019), reading comprehension (Lee et al, 2011) or in both decoding abilities and reading comprehension (Pritchard et al, 2009(Pritchard et al, , 2014Johnson et al, 2011;Leijon et al, 2016Leijon et al, , 2018. Similar results were found in two metaanalyses (Aarnoudse-Moens et al, 2009;Kovachy et al, 2015).…”
Section: Reading and Associated Abilities In Preterm Childrenmentioning
confidence: 63%
“…The comprehensive standardised test battery was identical at both assessments and demonstrated acceptable test–retest reliability. We had previous experience using these tests, which have been shown to discriminate between different types of reading disabilities in children and adolescents . Neonatal care has changed since our test cohort were born.…”
Section: Discussionmentioning
confidence: 99%
“…Data were initially collected at the end of first grade from VLBW children who were born in one of five hospitals . Of the 118 VLBW infants born in that region, 94 (80%) survived and eight were excluded: four because they lived in a geographically remote area and this made it hard to find matched controls, three because they were enrolled in school when the study started and one because their medical records were lost.…”
Section: Methodsmentioning
confidence: 99%
“…It has been frequently reported that girls outperform boys under 4 years of age (Harrison & McLeod, 2010;Reilly et al, 2009;Skeat et al, 2010;Zambrana, Pons, Eadie, & Ystrom, 2014) and girls and boys respond differently to known risks such as SES and parental input (Bornstein et al, 2004;Zambrana et al, 2014) whereas other studies have found no gender-based differences (Jackson, Schatschneider, & Leacox, 2014). Other child factors that have been found to be related to the acquisition of words are low birth weight (Leijon, Ingemansson, Nelson, Wadsby, & Samuelsson, 2016;Taylor et al, 2013), children's behaviour, and non-verbal cognitive skills (Beitchman et al, 2008;Law et al, 2012).…”
Section: Influences On Vocabulary Developmentmentioning
confidence: 99%